Pengaruh Kompetensi dan Pengembangan Karier terhadap Kinerja Pegawai Setjen DPDRI Pasca Pandemi - Putra, Dhani Pramulia Eka (Penerbit Goodwood, 2025)
Purpose: This study aims to examine the relationship between competence and career development and employee performance at the Secretariat General of the Regional Representative Council of the Republic of Indonesia (DPD RI). Methodology/approach: The study was carried out utilizing survey and quantitative methodologies at the DPD RI Secretariat General. Questionnaires were distributed to staff members to aid in the gathering of data. Multiple linear regression analyses were performed with SPSS software to assess the partial and simultaneous effects of the independent components (competence and career development) on the dependent variable (employee performance). Results/findings: According to the findings, professional growth and competence have a good and significant influence on employee performance. The regression coefficients for professional development and competence were 0.985 and 0.781, respectively, with p-values of 0.000. Both factors accounted for 69.4% of the variance in employee performance (R2 = 0.694). Conclusions: The findings indicate that at the DPD RI Secretariat General level, personnel performance may be considerably enhanced by enhancing staff knowledge and putting in place efficient career development programs. Limitations: This study focuses exclusively on internal traits like competency and career advancement, excluding external factors like leadership style and company culture. Contribution: This study enhances human resource management by providing empirical evidence on how competency and career development affect employee performance in the public sector. It would be extremely beneficial to legislators, human resource specialists, and scholars who are interested in public administration and organizational performance.